implementacion de una unidad didcatica basada en estrategias ludicas para el fortalecimiento del aprendizaje del algebra en grado octavo de la institucion educativa simom bolivar de buenaventura valle del cauca (2020)
The objective of the work was implemented a didactic unit that allows the eighth grade children of the I.E. Simón Bolívar de Buenaventura, internalize, apply and remember the Mathematical Concepts fear of the game. This implementation is carried out with the objective of improving the learning level of students in the subject of algebra. This work is presented by Knowledge and experience on innovation in Science Teaching and through 5 phases that involved the selection of students, the performance of a diagnostic test, the design of the didactic unit, its implementation and the Analysis of the Results when implementing it. This project was mixed due to the fact that qualitative tests were carried out through observation and data collection through tests that allowed measuring cognitive aspects. This study shows that the importance of innovation and play in secondary education is essential so that both the competencies of teachers and the interest of students are greater as they advance in Educational Areas, determining a better POSSIBILITY of better on personal and professional skills